Mainstreaming cooperative societies into peacebuilding knowledge networks for sustainable peace and development in Nigeria (2018)
Evidently, peace is a critical ingredient of socio-economic development in any polity. Unfortunately, the Nigerian State has become a theater of violence. Thus, socio-economic activities that could engender sustainable development of the nation are interrupted and hindered. The implication is that the top-down approach (track one diplomacy) for conflict prevention and peacebuilding in Nigeria needs to be complemented by the other tracks. In light of this, the question that looms large now is how do we energise the civil society to become an effective stakeholder in building peace in Nigeria? The paper examines how the nation's plethora of cooperative societies can be mainstreamed into peacebuilding knowledge networks for effective participation in peacebuilding activities. Qualitative data collected were interrogated using Stone’s elucidation of the rote of knowledge networks to articulate strategics for reinventing the nation’s cooperative societies to become effective agents for promotion of peacebuilding works. The paper concludes that these efforts would greatly strengthen the collaboration between the state and society. The collaboration, the paper shows, is required for effective implementation of peacebuilding initiatives meant to engender sustainable peace and development in the country.